Awareness of malocclusion and attitude towards orthodontic treatment among trainee dental surgery technicians in Nigeria - Otaren NJ (Ibom Medical Journal, 2024)
Objective: Malocclusion affects aesthetics, the physical, psychological and social life of a person. The aim of this study was to evaluate the awareness of malocclusion and attitude towards orthodontic treatment among trainee dental surgery technicians in Nigeria.